LIQUID INSULATING MATERIALS MOISTURE CONTENT CONTROL METHODS. CONDITION AND PROBLEMS - S. M. Korobeynikov; M. N. Lyutikova (Известия высших учебных заведений: Проблемы энергетики)
The article is dedicated to the issue of water influence on the main insulation of high voltage equipment and its technical condition in general. The article reviews modern methods of definition of moisture content of insulating liquids used in laboratories of public utilities. Their possibilities and limitations are provided. The attention is drawn to problems of metrological provision, performance technology and methods standardization. Prospective methods of moisture definition are provided. The article appraises the importance of relevant analysis results recovery in order to timely execute technical maintenance of high voltage equipment and its failure prevention.